Russia India China - Kundu, Nivedita Das (ed.) (New Delhi, 2010)
The idea of trilateral cooperation between Russia-India-China, launched in the 1990s, has been growing from strength-to-strength. The track one and half dialogue, which began with the meeting of the Foreign Ministers, culminated at the gathering of the heads of states of the three countries. Since 2001, experts, scholars and diplomats have met to demarcate areas of collaboration in various sectors. Trade and economic sector and energy security are the vital area for cooperation as all the three countries have registered the fastest growth rates in the world. They are equally concerned with issues of disarmament and non-proliferation. Conscious of the damage being caused to natural resources, Russia, India and China have sought to address the issue of restoring the environment and tackling climate change. While there are differences among these three countries, the areas where their interests converge are several. They hold similar views on multilateralism, giving primacy of place to a multi-polar world order, the need to democratise international relations and develop a just international system. They hold similar perspectives on the emerging threat of terrorism, the importance of promoting the regional cooperative mechanism to address the problems faced by the region, the challenges posed by globalisation, as well as new threats like the current financial crisis that have effected them to some degree or other.
Keywords: Russia(Federation)-Foreign relations-India